Bacillus aryabhattai LAD impacts rhizosphere bacterial community structure and promotes maize plant growth. (10th June 2022) - Deng, Chao; Zhang, Ning; Liang, Xiaolong; Huang, Tao; Li, Bingxue
Abstract: BACKGROUND: Plant growth‐promoting rhizobacteria may significantly impact the soil microbial community and the growth of plant roots and have critical roles in soil ecosystem functioning. However, the interactions between rhizobacteria and plants are extremely complicated and remain understudied. RESULTS: In this study, a Bacillus strain was isolated from a long‐term maize colonization soil and identified as Bacillus aryabhattai strain LAD. Laboratory tests showed that B. aryabhattai LAD had phosphate‐solubilizing and nitrogen‐fixing functions that benefit plant growth. The effects of LAD cultures on the root system development of corn seedlings and the structure of rhizosphere bacterial communities were studied. The most significant stimulations of LAD culture on plant growth were observed at a cell density of 10 2  CFU mL −1 . Treatment with LAD culture in hydroponics caused an increase of 107%, 197%, and 25% in the shoot length, total root length, and main root thickness respectively. The LAD treatment also significantly affected the rhizosphere microbial abundance and community structure. The rhizobacterial abundance and species richness in the corn seedlings treated with LAD culture were significantly lower than those in the control group. However, the LAD‐treated samples had higher relative abundances of plant growth‐promoting rhizobacteria like Bacillus and Burkholderia than the control samples did, suggesting that LAD treatment may facilitate the mutualistic relation between the rhizosphere microbiome and the plant. CONCLUSION: These results collectively demonstrated that LAD is capable of shaping the rhizosphere microbial community structure and functions as a plant growth‐promoting agent, which makes it a strong candidate for application as bio‐fertilizer in agricultural systems. © 2022 Society of Chemical Industry.